Kinerja Perusahaan dari Perspektif Karakteristik Komite Audit - Nurmawati, Ulmi; Survira, Azelly; Yuddin, Ahmad Falqi; Hartono, Arvin Bhadrika; Zaitul, Zaitul (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
Company performance is a condition in a certain period caused by operating activities and the use of available resources. The goal of this research is to determine how audit committee attributes, such as independence, experience, size, meetings, and audit quality, affect business performance in the building construction subsector for companies listed on the Indonesia Stock Exchange (IDX) in 2021–2022. Tobin's Q is employed as a stand-in for evaluating firm performance, and 34 observations and 17 company samples are used to meet the research objectives based on the chosen sample criteria. The findings of the study indicate that audit quality, audit committee size, and the independence of audit committees significantly impact business success. However, the frequency of audit committee meetings and the expertise of committee members do not appear to influence the organization’s performance. This suggests that while factors such as the quality of audits, the size of the audit committee, and its independence are crucial for ensuring effective oversight and better business outcomes, aspects like meeting frequency and member expertise may not be as critical in directly affecting organizational success. For businesses, this implies that prioritizing these key elements such as audit quality and an independent and adequately sized committee could be more beneficial than focusing on the number of meetings or the specific expertise of committee members. From a regulatory standpoint, this finding might influence policies to focus on strengthening the independence and size of audit committees rather than solely emphasizing meeting frequency or expertise.